Peran Partai Boshelvik dalam Revolusi 1917 Dibawah Pimpinan Vladimir Lenin - KRISTINAWATI, PUTRI (Politeia: Jurnal Ilmu Politik, 2013)
Russia as a socialist state is an important part of the history of the world. The history show Vla-dimir Lenin dan Boshelvik Party had successfully apply revolution theory which pioneered by Karl Marx. This study discusses about the steps are applied Lenins revolution and the Party Boshelvik to reach revolution (1917) in Russia. This study is using historical aproach (political history). Colecting data of this study is using secondary data which is obtained from books, lit-erature and document. The analysis using descriptive analysis. The findings ofthis study, there are two stages of revolution that Lenin and the Party Boshelvik applied. First, Bourgeois Revo-lution, pioneered by bourgeoisie and labourer/peasant to bring down the feudal system (Tsar) Russians; Second, socialist revolution, pioneered by the proletariat with all workers to bring down the bourgeois system.Keywords: Political Party, Bourgeoisie Revolution, Socialist revolution.